2019
DOI: 10.1002/jcla.23003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of differential expression profile of miRNA in peripheral blood of patients with lung cancer

Abstract: Purpose To identify potential molecular targets for lung cancer intervention and diagnosis, we analyzed the differential miRNA expression of peripheral blood between lung cancer patients and healthy controls. Methods Three pairs of cases’ and controls’ peripheral blood samples were evaluated for miRNA expression by microarray. 12 miRNAs were selected for RT‐PCR validation and target genes prediction. In addition, 4 miRNAs were selected for future validation by RT‐PCR in a large sample of 145 cases and 55 frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 28 publications
(44 reference statements)
3
28
0
Order By: Relevance
“…High expression of this miRNA in vitreous and serum could provide insight into its role, although further study is needed to analyze the its function. Since only very few miRNAs and their target genes have been identified, and the functions of most miRNAs remain unclear [73], such insight into the interplay of miRNAs in VRL would help further steer rational diagnostic and therapeutic strategies and ultimately improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of this miRNA in vitreous and serum could provide insight into its role, although further study is needed to analyze the its function. Since only very few miRNAs and their target genes have been identified, and the functions of most miRNAs remain unclear [73], such insight into the interplay of miRNAs in VRL would help further steer rational diagnostic and therapeutic strategies and ultimately improve patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This method is often used to validate data obtained from microarray, as reported i.e. by He et al, which analyzed the differential expression profile of miRNAs in peripheral blood of lung cancer patients [66]. RT-qPCR technique include both TaqMan and SYBR green assays.…”
Section: Reverse Transcription Quantitative Pcrmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a type of endogenous noncoding small RNAs with a length of about 19-23 nucleotides [8]. To regulate the expression of their target genes at the post-transcriptional level, mature miRNAs mainly suppress the translation of their target mRNA by complementary base pairing [9]. miRNAs present in the fluids including urine, serum, plasma, tear and amniotic fluid, and they can resistant to harsh conditions [10].…”
mentioning
confidence: 99%
“…miRNA also present in exosomes which can be taken up by neighboring or distant cells and subsequently modulate recipient cells [11]. So miRNAs could be a marker of intervention and diagnosis, such as hsa-miR-135a-5p, hsa-miR -542-3, and hsa-miR-4491 maybe the intervention and diagnosis marker of lung cancer via blood test [9]. It has also shown that miRNA can bind to hundreds of target mRNAs and play regulatory roles in almost all mammalian pathological and physiological activities.…”
mentioning
confidence: 99%
See 1 more Smart Citation